If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 = -3 + -10x + 7x Reorder the terms: -3 + x = -3 + -10x + 7x Combine like terms: -10x + 7x = -3x -3 + x = -3 + -3x Add '3' to each side of the equation. -3 + 3 + x = -3 + 3 + -3x Combine like terms: -3 + 3 = 0 0 + x = -3 + 3 + -3x x = -3 + 3 + -3x Combine like terms: -3 + 3 = 0 x = 0 + -3x x = -3x Solving x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. x + 3x = -3x + 3x Combine like terms: x + 3x = 4x 4x = -3x + 3x Combine like terms: -3x + 3x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| -13+5x=x-1 | | 10n+15=9n+6n | | (3x^3/z)^3 | | 6x+21=7(x+3) | | 1-4k=-5k-1 | | -6-a=1+6a | | 5x-3=10x | | -5k+10k+16=1+2k | | -12x-14=-74 | | 5(8+7c)=390 | | 3x+15x+7=162 | | 7a-2=10+7a+4a | | 3/5x-2/3 | | 3/5x-2/5 | | -2+5v=9v+10 | | 12-9b=6-8b | | 2u+8u-5u= | | An=1/27*3^n-1 | | 1-8x=-7-6x | | 3/5x-2/5=3/10 | | -(3x-3)=-6-2x | | 17-9n=1-7n | | 4/3=v/8 | | 2x-5x=-5-2x | | 3r-6=2r-2r | | 0=3b+21 | | 1+3p=-4p+15 | | -18+7m=m-6-6 | | Y/3-3=11 | | 6n-14=4n+16 | | k-6=m+18 | | 3x=y+16 |